O problema de Dirichlet para a equacão dos gráficos mínimos com dado no bordo lipschitz contínuo - Assmann, Caroline Maria (2016)
In this work, we study existence and non existence for the Dirichlet problem for the minimal graph equation in non convex domains of the plane. We search for conditions on the boundary data which be the less restricted possible for the solubility of the Dirichlet problem.